Análisis de decisión de inversión sobre valor futuro y colaterales a mediano y largo plazo. - Bustamante Preciado, Bryan Fernando (My University, 2021)
This research project is a work of analysis and bibliographic scientific review, of secondary and primary data when verifying the resolution of the case, in addition to a descriptive quantitative analysis which aims to demonstrate according to the parameters established and provided in the case of study results of the established operation. Within the analysis and solution of the same it was possible to determine that the balance of the operation is favorable to the client according to the parameters given in the case, since it remains with a positive balance in its favor, it should be noted that the values ​​that have been taken in account, both in percentage rates for credit and for investment, are current real data that govern the control entities of the country's current financial system, giving a real perspective to the resolution of the research work, which may vary according to the rates subject to in return too. The objective of this research work is to determine the appropriate investment option according to the regulations of the current financial system, and it was decided to choose the rates given according to the segment to which the client belonged according to the parameters of the case.
El presente proyecto de investigación es un trabajo de análisis y revisión científica bibliográfica, de datos secundarios, y primarios al constatar la resolución del caso, además de un análisis cuantitativo descriptivo el cual pretende demostrar según los parámetros establecidos y brindados en el caso de estudio los resultados de la operación establecida. Dentro del análisis y solución del mismo se pudo determinar que el saldo de la operación es favorable al cliente según los parámetros dados en el caso, ya que se queda con un saldo positivo a su favor, cabe recalcar que los valores que se han tomado en cuenta, tanto en tasas porcentuales para crédito y para la inversión son datos reales actuales que rigen en los entes de control del sistema financiero vigente del país, dando una perspectiva real a la resolución del trabajo de investigación, la cual podrá variar según la tasas sujetas a cambio también. El objetivo del presente trabajo de investigación es determinar la opción adecuada de inversión según la normativa del sistema financiero vigente, y se optó por escoger las tasas dadas según el segmento al que pertenecía el cliente según los parámetros del caso.
Keywords: VALOR FUTURO; INVERSIONES; MERCADO FINANCIERO